Preclinical evaluation of CXCR4 peptides for targeted radionuclide therapy in glioblastoma - Anthony Waked; Melissa Crabbé; Virginie Neirinckx; Sunay Rodriguez Pérez; Jasmien Wellens; Bernard Rogister; M. Abderrafi Benotmane; Koen Vermeulen (SpringerOpen, 2024)
Abstract Background Glioblastoma (GBM), is the most fatal form of brain cancer, with a high tendency for recurrence despite combined treatments including surgery, radiotherapy, and chemotherapy with temozolomide. The C-X-C chemokine receptor 4 (CXCR4) plays an important role in tumour radioresistance and recurrence, and is considered as an interesting GBM target. TRT holds untapped potential for GBM treatment, with CXCR4-TRT being a promising strategy for recurrent GBM treatment. Our study focuses on the preclinical assessment of different 177Lu-labelled CXCR4-targeting peptides, CTCE-9908, DV1-K-DV3, and POL3026 for GBM treatment and exploring some of the radiobiological mechanisms underlying these therapies. Results All three DOTA-conjugated peptides could be radiolabelled with 177Lu with > 95% radiochemical yield. Binding studies show high specific binding of [177Lu]Lu-DOTA-POL3026 to U87-CXCR4 + cells, with 42% of the added activity binding to the membrane at 1 nM, and 6.5% internalised into the cells. In the presence of the heterologous CXCR4 blocking agent, AMD11070, membrane binding was reduced by 95%, a result confirmed by quantitative in vitro autoradiography of orthotopic GBM xenograft sections. An activity-dependent decrease in cell viability was observed for [177Lu]Lu-DOTA-DV1-K-DV3 and [177Lu]Lu-DOTA-POL3026, along with a slight increase in the induction of apoptotic markers. Additionally, the expression of γH2AX increased in a time-and activity-dependent manner. Ex vivo biodistribution studies with [177Lu]Lu-DOTA-POL3026 show uptake in the tumour reaching a SUV of 1.9 at 24 h post-injection, with higher uptake in the kidneys, lungs, spleen, and liver. Dosimetry estimations show an absorbed dose of 0.93 Gy/MBq in the tumour. A blocking study with AMD11070 showed a 38% reduction in tumour uptake, with no significant reduction observed in µSPECT imaging. Although no brain uptake was observed in the ex vivo biodistribution study, autoradiography on U87-CXCR4 + tumour inoculated mouse brain slices shows non-specific binding in the brain, next to high specific binding to the tumour. Conclusions In conclusion, we compared different 177Lu-radiolabelled CXCR4-targeting peptides for their binding potential in GBM, and demonstrated their varied cytotoxic action against GBM cells in vitro, with POL3026 being the most promising, causing considerable DNA damage. Though the peptide's systemic biodistribution remains to be improved, our data demonstrate the potential of [177Lu]Lu-DOTA-POL3026 for CXCR4-TRT in the context of GBM.